A Sociolinguistic Analysis of Variation in a Rural African Community - Yohana, Rafiki (Linguistics, 2014)
This study mainly investigates whether language variation due to sociolinguistic stratification in Western urban speech communities is similar to that in rural African communities, using as a case study the multilingual Chasu of Same district in Kilimanjaro Tanzania. Primarily, the study addresses the question of language use and variation in a multilingual context in which an analysis of the frequency of occurrence of lexical borrowings and code-switching from Swahili and English is undertaken. The study firstly investigates whether the key sociolinguistic variables of social class, gender, style, age and educational levels have as much bearing in explaining the occurrence of code-switching and lexical borrowings in multilingual Chasu. Secondly, the study examines whether social stratification correlates with the phonological variables (s) and (z) in Chasu, along lines established in Western variationist sociolinguistics. In order to obtain a valuable representative sample of data, the 'Labovian' model of the sociolinguistic interview incorporating narratives of personal experience was used. Other complementary techniques such as participatory observation and rapid surveys with wordlists and questionnaires are employed as well. In the context of language contact, the analysis demonstrates that highly educated, young and middle-class speakers are the ones who borrow words and code-switch from word to sentence levels from Swahili and sometimes from English. Through VARBRUL and Rbrul analysis of phonological variation this study reveals further that, while in Western urban communities social factors particularly social class - have significant impact on language variation and change, in Chasu society internal structural factors are the ones that are more influential. Education attainment is a prime external factor in regulating the use of standard variants [z] and [s] against non-standard variants [Ã°] and [Î¸] respectively. However, such external social factors are significant only when associated with syllable position, vowels following the variables or the status of the lexical item-i.e. whether a word is borrowed from Swahili or native Chasu words.